Análise da influência de corpos d'água em microclimas urbanos: estudo de caso em São José do Rio Preto, SP - Masiero, Érico (Universidade Federal de São Carlos, 2014)
This study analyzes the microclimate effects caused by a water body in São José do Rio Preto city, which is located at an Altitute Tropical Climate region in the São Paulo State, Brazil. The main hypothesis stems from the conjunction among the air masses action in the region combined with the evaporative cooling by the water body in the built environment. The study methodology is based on the physical characterization of different environments that make up the urban environment, in determining procedures of gathering data field, in the analysis of macro and meso climatic characteristics of the region, in the treatment of microclimate data by mapping information and the formulation of guide lines for urban space occupation. The monitoring field data campaigns used meteorological measurements at fixed points to record the behavior of temperature, humidity, solar radiation, evapotranspiration, the wind speed and direction in the urban area, both in the rural environment, in the bank of the dam, in the inner city and in the suburbs. Climate general information of the region were collected by Automatic Weather Station of CIIAGRO Center for Integrated Agricultural Weather Information and the CETESB Station Environmental Company of São Paulo State - which were crossed with the data and the satellite images of INPE-CPTEC Prediction Center of Weather and Climate Research. After the field campaigns, climatic data and physical characteristics of the urban environment were processed using geostatistical methods for mapping the microclimate behavior of the studied urban areas. We concluded that the wind action over the water mass may influence the immediate surroundings, reaching approximately 1.000m depending of the topographical characteristics, of the urban occupation and the atmospheric conditions. Humidification of urban air through the water body can reduce the daily temperature peaks at approximately 3°C, however, the significant difference found in the rates of temperature and humidity in the urban canopy layer clarifies that the 9 km² of the water surface are insufficient to influence the farthest outlying areas of the dam under any climatic conditions. The low penetration of humidified air masses suggests that urban space should favor the passive action of evaporative cooling to cause microclimatic effects to mitigate the temperature amplitude in low vegetated areas and in a highly waterproofed city.
Keywords: Engenharia urbana; Ventilação urbana; Resfriamento evaporativo; Microclimas; Water body; Urban ventilation; Evaporative cooling; Microclimate; ENGENHARIAS